Puerperal sepsis: An integrative review (Research, Society and Development, 2021)
In 2016, the concept of sepsis was redefined, however it still needs to be better characterized. In Brazil, this complication has a mortality of 28% and costs of approximately 9,100 dollars per patient. Given the difficulties of definition and diagnosis, this work aims to synthesize available scientific evidence. This is an integrative review carried out between January and June 2021, to answer “What is the recent evidence about puerperal sepsis?”. The search considered the last 5 years and resulted in 53 articles, of which 14 were selected due to the exclusion criteria. Of these, 28.6% are guidelines, 64.3% are observational studies and 7.1% are experimental. Regarding the countries of publication, more than 50% were carried out in the USA (35.75%) and England (14.3%). As for the language of the publications, 78.5% were written in English; 14.3% in Spanish, and 7.2% in Portuguese. Puerperal sepsis remains one of the main causes of morbidity and mortality worldwide. The pathophysiology is not fully understood, and scientific evidence is lacking, especially regarding early diagnosis and treatment. Regarding the diagnosis, the physiological changes of pregnancy end up masking the clinical picture and making the investigation challenging. Thus, anamnesis and physical examination are still essential, aided by complementary exams. Treatment aims at early recognition and aggressive intervention through antibiotic therapy, fluid replacement and cardiovascular support.